My Liberating Approach to Teaching and the Howabouts of Its Transforming Power - Seyed Mohammad Hassan Hosseini (IJOTL-TL (Indonesian Journal of Language Teaching and Linguistics))
This paper attempts to throw into sharp relief my liberal instructional approach, Competitive Team-Based Learning, and shed light on its design, objective, syllabus, materials, and tasks. It also gives a glimpse of the significance of my pedagogical approach for today's world context of globalization, which is characterized by despotism, capitalism, and imperialism. Most importantly, the paper explicates the howabouts of my liberating approach transforming power and highlights its distinguishing features and characteristics with reference to the present methods and approaches like CLT and particularly CL methods.